The Impact Evaluation of Vietnam's Escuela Nueva (New School) Program on Students' Cognitive and Non-cognitive Skills - Hai-Anh Dang; Paul Glewwe; Jongwook Lee; Khoa Vu (Institute of Labor Economics (IZA), 2022)
This paper evaluates how Vietnam's Escuela Nueva (VNEN) program, an educational reform for primary schools supported by the World Bank, affected the cognitive (mathematics and Vietnamese) and non-cognitive (socioemotional) skills of students in that country. We use propensity score matching to estimate both short-term (1-3 years) and long-term (5-7 years) average treatment effects on the treated (ATT). We find that the impacts of VNEN on students' cognitive skills are relatively small in the short-term, and that they are larger for boys, ethnic minorities, and students in Northern Vietnam. The VNEN program modestly increased primary school students' non-cognitive skills in the short-term; these impacts on non-cognitive skills are sizable and significant for ethnic minority students, although there seems to be little gender difference. The long-term impacts are less precisely estimated, but they appear to fade away, showing little or no impact of the VNEN program on cognitive skills. There is little variation of long-term impacts by gender or geographical region, although the imprecision of the estimates for ethnic minority students does not allow us to rule out large long-term impacts on cognitive skills for those students. The program's impacts on non-cognitive skills also seem to have dissipated in the long-term.
Keywords: I2; O1; 330; VNEN; Vietnam Escuela Nueva; education; cognitive skills; non-cognitive skills; impact evaluation; propensity score matching; IV